2001
DOI: 10.1289/ehp.109-a18b
|View full text |Cite
|
Sign up to set email alerts
|

Too clean for comfort.

Abstract: Scientists are going to discover many subtle genetic factors in the makeup of human beings. . . . Once we can say that there are differences between people that are easily demonstrable at the genetic level, then society will have to come to grips with understanding diversity-and we are not prepared for that.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The trend profile of these specific dioxin congeners did not correlate with the trend profile of the higher-chlorinated dioxin homologues or any chlorinated furan homologues, suggesting a unique source. These results are fully consistent with the phototransformation of triclosan and its chlorinated derivatives that form during wastewater chlorine disinfection as the source of 2,8- DCDD,2,3,1,2,and 1,2,3, environment. As the levels of triclosan-derived dioxins increased over time and the total level of chlorinated dioxins decreased, the contribution of triclosan-derived dioxins to the total dioxin pool increased to as high as 31% by mass in recent years, indicating that their contribution to total dioxin toxicity may need consideration.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The trend profile of these specific dioxin congeners did not correlate with the trend profile of the higher-chlorinated dioxin homologues or any chlorinated furan homologues, suggesting a unique source. These results are fully consistent with the phototransformation of triclosan and its chlorinated derivatives that form during wastewater chlorine disinfection as the source of 2,8- DCDD,2,3,1,2,and 1,2,3, environment. As the levels of triclosan-derived dioxins increased over time and the total level of chlorinated dioxins decreased, the contribution of triclosan-derived dioxins to the total dioxin pool increased to as high as 31% by mass in recent years, indicating that their contribution to total dioxin toxicity may need consideration.…”
supporting
confidence: 85%
“…One of the solar photolysis products of triclosan in water, however, is the chlorinated dioxin, 2,8dichlorodibenzo-p-dioxin (2,8-DCDD) (15)(16)(17) (Figure 1). Analogous to triclosan, 4-Cl-TCS, 6-Cl-TCS, and 4,6-Cl-TCS photochemically react to form 2,3,7-trichlorodibenzo-pdioxin (2,3,7-TriCDD), 1,2,8-trichlorodibenzo-p-dioxin (1,2,, and 1,2,3,8-tetrachlorodibenzo-p-dioxin (1,2,3,8-TCDD), respectively, under solar irradiation (Figure 1) (15,18). The dioxin products from the CTDs are potentially of greater concern than 2,8-DCDD formed directly from triclosan, because dioxin receptor binding/toxicity increases with chlorine substitution in the lateral positions (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Kitchen sink drains are arguably one of the most highly biocide-exposed environments, owing to the widespread use of antimicrobial-containing domestic detergents (46). An important part of this study involved determining the effects of QD on bacterial susceptibilities to QAC and selected chemically unrelated antibiotics and biocides.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decade, the broad spectrum of antimicrobial activity displayed by TCS has led to its application in a range of formulations intended for domestic use, including a variety of shampoos (26), toothpastes (40), deodorants (7), detergents, molded plastic containers, and chopping boards. A survey of liquid soaps in the United States revealed that 45% contained antibacterial agents, many of which included TCS (51). Recently, the particular use of hardware products that contain TCS has increased considerably (7).…”
mentioning
confidence: 99%